Wykorzystanie metody DEA do alokacji środków finansowych NFZ w zamkniętej opiece zdrowotnej - Karwacki, Zbigniew (Application of a DEA Method to the Allocation of the NFZ (National Health Care Fund) Financial Resources to In-Patient Health Care, 2007)
Allocation is a decision making process with inevitable, competitive goals that have to be reached in conditions of limited economic resources. Decisions taken concern some ways of taking advantage of these resources and the allocation outcome may be of spatial dimension. There can be distinguished two points of view in the process of health care financing: one connected with supply and the other with demand. In the former, the main factor of the financial resources allocation is the size of infrastructure and number of staff, whereas in the latter, it is the size of health needs. In Poland the financing of in-patient health care from the NFZ resources is a two-stage process. The first stage combines financial resources divided among the NFZ units, in the second one the divided resources are allocated to the vendors within each unit. This paper presents an attempt to apply the DEA method to the process of taking optimum decisions in the second stage of financing of inpatient health care.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 111-121